The Meaning of the Good Faith Principle - Kullolli , Brunela (International Journal of Membrane Science and Technology, 2023)
The definition of good faith, which is difficult to define since it is vague, is covered in this paper before giving a thorough summary of the idea. The next section of the essay summarizes Good Faith throughout history, noting how its meaning has changed through time. The problematic facets of the idea of "Good Faith" are discussed in the third section of the essay. This section examines how the difference between objective and subjective notions of trust, which poses a challenge in any society, is problematic for various legal systems. Similarly, the fourth part of the study examines the applicability of Good Faith in contract law and as a concept of contractual interpretation. In countries with civil law, it is maintained that there is a general need to bargain in good faith; however, the specifics of this requirement vary depending on the specific legal system. The centrality of the idea of good faith in numerous legal, philosophical, and moral situations is highlighted in this paper's conclusion. Acting in good faith is crucial for upholding trust and fairness in our interactions with others, despite much controversy surrounding its definition and understanding. In contrast to some professors' opinions that the word "in good faith" should be enforced in order to preserve precedent, it might be more appropriate to publicly authorize which the court may modify, supplement, and bolster the code as required. Despite the fact that there have been disagreements about it, Albania must further establish the good faith thesis. This calls for discussions between lawyers and academics as well as the development of civil procedure..